2012
DOI: 10.1080/00224499.2011.598248
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Onset of Sexual Behavior and Sexual Risk in Youth Perinatally Infected with HIV

Abstract: Perinatally HIV-infected (PHIV+) youth are surviving into adolescence and young adulthood. Understanding the sexual development of PHIV+ youth is vital to providing them with developmentally appropriate HIV prevention programs. Using pooled data (N = 417) from two longitudinal studies focused on HIV among youth (51% female; 39% HIV+) and their caregivers (92% female; 46% HIV+), we compared the rate of sexual onset during adolescence across four youth-caregiver combinations: PHIV+ youth with HIV+ caregivers (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 37 publications
4
35
2
Order By: Relevance
“…8,[33][34][35] Nine studies had HIV-uninfected counterparts as part of the analytic sample to serve as a comparison group. 14,25,28,31,[36][37][38][39][40] Ten studies focused on samples of only young women, 8,9,14,19,25,28,31,33,39,41 while the remainder had samples that included both young men and women. Eight studies included only BHIV.…”
Section: Set Of Manuscriptsmentioning
confidence: 99%
See 3 more Smart Citations
“…8,[33][34][35] Nine studies had HIV-uninfected counterparts as part of the analytic sample to serve as a comparison group. 14,25,28,31,[36][37][38][39][40] Ten studies focused on samples of only young women, 8,9,14,19,25,28,31,33,39,41 while the remainder had samples that included both young men and women. Eight studies included only BHIV.…”
Section: Set Of Manuscriptsmentioning
confidence: 99%
“…8,9,19,21,[25][26][27][28] Because of a recently published review article on PHIV adolescents, 7 we only included eight articles focused on just PHIV. 33,[35][36][37][38][40][41][42] Those were published since the review or were outside the scope of the review; one was included in the review, but is highlighted here from a different perspective. 41 The remaining studies 670 CARTER ET AL.…”
Section: Set Of Manuscriptsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Some researchers examining PHIV + youths' sexual behaviors have found rates of sexual activity to be the same or lower than in other populations, with a delayed age of onset. [7][8][9] In contrast, other studies and clinical data suggest that there is a group of PHIV + youth who are initiating sexual activity early and engaging in unprotected sex in combination with other HIV risk behaviors such as substance use. 10,11 One cross-sectional study found that 33% of 13-to 24-year-old PHIV + youths had initiated vaginal intercourse, 35% of whom had reported their first occurrence before age 16 years.…”
mentioning
confidence: 97%